Pengaruh Ekspor Migas dan Non Migas Terhadap Posisi Cadangan Devisa di Indonesia - Muhammad Umar Maya Putra; Syafrida Damanik (Jurnal Wira Ekonomi Mikroskil, 2017)
Every country wants to get welfare. To get welfare, in the context of foreign conduct international trade. Instruments used in international trade is exports that can be used as a driving force in promoting economic development. A difference of a factor of production (endowment) would enable exports done so between countries will create profits respectively. Exports made by Indonesia in the form of oil and gas and non-oil can help the economy and could add to reserves through other countries. In the time series data 2005 to 2012 by using SPSS 16 the result is that oil and gas exports and a significant positive effect on the foreign exchange reserves but otherwise non-oil exports and no significant negative effect on foreign exchange reserves.